Analisis Kesalahan Siswa dalam Menyelesaikan Soal Cerita Berdasarkan Tahapan Newman dan Upaya Pemberian Scaffolding - Upu, Angreny; Taneo, Prida N. L.; Daniel, Farida (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2022)
This study aims to analyze student errors in solving story problems based on Newman's stages and provide scaffolding to minimize errors made by students. The subjects in this study were 19 students of class VIII4 SMPN 1 Mollo Utara. The method used in this research is descriptive qualitative. Data collection techniques using observation, tests and interviews. The data analysis technique is by the Miles and Huberman model where the validity of the data is tested by technical triangulation. The results showed that the errors made by students in solving story problems based on Newman's stages were misunderstandings, transformation errors, process skills errors and notation errors which were respectively 47,37%; 5,7%; 26,31% and 21,05% of students. A form of error that students did not make at all was a reading error. The scaffolding strategy applied by the teacher to the students to overcome these errors is the strategy of explaining and reviewing the types of errors in understanding, transformation and notation as well as the strategy of explaining, reviewing, and restructuring on the types of errors in process skills. Providing scaffolding in the form of teacher assistance that is explaining, reviewing and restructuring in response to student errors can encourage most students to no longer make mistakes while some students are still wrong when solving problems after being given scaffolding but the error rate is lower than before.